Active Ingredients of Interventions Improving Smoking Cessation Support by Dutch Primary Care Providers: A Systematic Review. Issue 1 (March 2023) - Mergelsberg, Enrique L. P.; de Ruijter, Dennis; Crone, Mathilde R.; Smit, Eline S.; Hoving, Ciska
The objective was to assess active ingredients, change mechanisms, and fidelity in interventions aiming to increase the quality of smoking cessation care in the Dutch primary healthcare setting. We conducted a systematic review searching five scientific databases on August 2nd, 2019, updated on October 28th, 2021. We included effect data of behavioural interventions aiming at improving the provision of smoking cessation support by Dutch primary care providers to their patients. We excluded studies published before 2000 and those without a behavioural support intervention for primary care providers targeting smoking cessation in their patients. We found 1939 articles and included 15 distinct interventions in the review. We provided an overview of study characteristics, intervention effects, fidelity, active ingredients and change mechanisms using the Behaviour Change Techniques (BCT) Taxonomy and Mechanisms of Action (MoAs) protocols. Interventions seemed more effective when including a face-to-face component, using active learning strategies and providing a tool to help follow the guidelines in practice (e.g., physical cards with information). BCTs, MoAs, and fidelity were overall poorly reported on. To support the application of smoking cessation practices in Dutch primary care, we recommend implementation of face-to-face training programs incorporating active skill training elements combined with practical tools.